The Impact of Motivation, Work Discipline, and Workload on Employee Job Satisfaction at PT Haleoyora Powerindo Surabaya - Thomas Ferdiansyah; Acep Samsudin (Lavish Opulent Education, 2025)
This study aims to analyze the influence of motivation, work discipline, and workload on employee job satisfaction at PT Haleyora Powerindo Surabaya. Motivation serves as the primary driver of work enthusiasm, affecting employee satisfaction. Work discipline reflects adherence to rules and responsibilities in the workplace, while workload relates to the quantity and complexity of tasks assigned to employees. This research employs a quantitative approach using multiple linear regression methods to analyze the data. The results indicate that motivation and work discipline have a significant positive effect on job satisfaction, whereas workload has a negative impact. The findings suggest that management should enhance motivational strategies, enforce work discipline, and manage workloads effectively to improve employee satisfaction and productivity.